A Facile Green Synthesis of Chromene Derivatives as Antioxidant and Antibacterial Agents Through a Modified Natural Soil. Issue 17 (1st May 2019) - Mashhadinezhad, Maryam; Mamaghani, Manouchehr; Rassa, Mehdi; Shirini, Farhad
Abstract: A convenient, one‐pot multi‐component methodology was developed for the preparation of tetrahydro‐4 H ‐chromene and dihydropyrano[ c ]chromene derivatives as important biologically active compounds using nanoporous Na + ‐montmorillonite perchloric acid as a modified natural soil. All desired products were prepared with high yield in short times. The synthesized compounds were screened for their biological activities. In vitro antioxidant activity of the synthesized compounds was studied by 2, 2‐azinobis(3‐ethylbenzothiazoline‐6‐sulfonic acid) (ABTS) assay. The results showed that some compounds possess significant antioxidant activities (IC50 = 0.11 – 0.51 μM) in comparison to ascorbic acid as standard. The antimicrobial activity of these compounds was also investigated against four bacterial strains including Micrococcus luteus, Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli and structure‐activity relationships were established. The results revealed that some of the compounds exhibited significant activities compared to the standard drugs. Ease of preparation of reagent and bioactive products, simple work‐up, suitable reaction times, high yields and reusability of the reagent are noteworthy advantages of this method. Also, it is worth mentioning that clays have a natural origin and are found abundantly in nature. For this reason, they are cheaper than other nanomaterials and the processes performed by them will be more affordable. Abstract : A facile and eﬃcient synthesis of bioactive chromene derivatives was promoted by a modified natural soil and their biological activity was investigated. The antioxidant activity of the products was evaluated using the ABTS assay. The results showed that more compounds exhibited high radical scavenging activity in comparison to vitamin C as standard. The antimicrobial activity of these compounds was also investigated against four bacterial strains and the structure‐activity relationships of the samples were studied.